Current Issues in Vietnamese Linguistics (MDPI - Multidisciplinary Digital Publishing Institute, 2026)
This Reprint, part of the International Symposium on Vietnamese Linguistics (ISVL) series, brings together ten revised papers originally presented at the 4th and 5th ISVL workshops, hosted by National Yang Ming Chiao Tung University in 2024 and Ca’ Foscari University of Venice in 2025. Earlier ISVL meetings and companion volumes have mapped the field and set out broad directions for research; this Reprint continues that work with a set of focused studies that highlight both theoretical and empirical advances. These contributions examine a wide range of topics in Vietnamese linguistics, including the Austroasiatic inheritance of the language, the historical development of negation and the interaction of Sino-Vietnamese prefixes with sentential negators, reduplication and its interpretive effects, clause structure and locative inversion, the organization of the left periphery, reference and binding, null possessors in kinship and body-part terms, and the semantics and pragmatics of particles. Together, these papers provide new data, testable analyses, and comparative insights that connect Vietnamese to central debates in typology, historical linguistics, cartography, binding theory, and the semantics–pragmatics interface. The Reprint offers a concise but wide-ranging resource for scholars interested in the structure and history of Vietnamese and its role in broader linguistic theory.